pDomus: a prototype for cluster-oriented distributed hash tables - Rufino, José (2007)
The Domus architecture for Distributed Hash Tables (DHTs) is specially designed to support the concurrent de- ployment of multiple and heterogeneous DHTs, in a dy- namic shared-all cluster environment. The execution model is compatible with the simultaneous access of several dis- tributed/parallel client applications to the same or different running DHTs. Support to distributed routing and storage is dynamically configurable per node, as a function of appli- cations requirements, node base resources and the overall cluster communication, memory and storage usage. pDomus is a prototype of Domus that creates an envi- ronment where to evaluate the model embedded concepts and planned features. In this paper, we present a series of experiments conduced to obtain figures of merit i) for the performance of basic dictionary operations, and ii) for the storage overhead resulting from several storage technolo- gies. We also formulate a ranking formula that takes into account access patterns of clients to DHTs, to objectively select the most adequate storage technology, as a valuable metric for a wide range of application scenarios. Finally, we also evaluate client applications and services scalabil- ity, for a select dictionary operation. Results of the overall evaluation are promising and a motivation for further work.